Peculiarities of chemo-resistant HIV/AIDS-associated tuberculosis in patients who died from co-infection - A. S. Shalmin; E. M. Raznatovskya; R. М. Yasinskiy (Zaporozhye State Medical University, 2013)
Introduction. Today the problem of spread of two epidemics - TB and HIV/AIDS is too complicated in Ukraine. This problem is significantly complicated by the spread of the other world's problem - resistant TB. The growth of the HIV epidemic influences the situation of multidrug-resistant tuberculosis (MRTB), which is also associated with disorders of antituberculosis immunity. According to the literature, the high incidence of MRTB is directly correlated with the prevalence of HIV infection and AIDS. Tuberculosis is the direct cause of death of up to 30.0% of patients with HIV infection and in 90.0% cases of AIDS. That's why studying the clinical course of HIV/AIDS-associated tuberculosis and analysis of causes of death of these patients are highly actual today. The aim of the study. To determine the clinical course and causes of death in patients with chemo-resistant HIV/AIDS-associated tuberculosis. Materials and methods. 14 patients cards who died from chemo-resistant HIV/AIDS-associated tuberculosis and who were supervised and treated at Zaporizhzhya TB dispensaries during the period of 2010-2012 are analyzed in this article. The results of research. Among patients with chemo-resistant HIV/AIDS-associated tuberculosis there were 12 men (85.7%) and 2 (14.3%) women. The average age was 41.9 ± 1.8 years. There were 100% of unemployed patients, 8 patients (57.1%) were former prisoners, 4 (28.5%) patients were shelterless persons, 4 patients (28,5%) suffered from drug addiction and alcoholism. Antisocial lifestyle was in 8 (57.1%) cases. HIV-infection started significantly (P <0.05) more often after tuberculosis (in 8 patients (57.1%), before tuberculosis - in 2 (14,4%) patients, the simultaneous detection of co-infection was found in 4 cases (28,5%). Chemo-resistant HIV/AIDS-associated tuberculosis was found in patients with primarily diagnosed HIV/AIDS-associated tuberculosis in 2 cases (14.3%), with recurrent tuberculosis - in 2 (14.3%), with chronic tuberculosis - in 10 (71.4%). As it was noticed, the chronic process prevailed significantly (P <0.05) in patients who died from resistant co-infection. Among patients with MRTB patients who were resistant to 6-9 antitubercular drugs prevailed - 8 cases (66.7%), compared with patients with resistance to 4-5 antitubercular drugs - in 4 cases (33.3%). Among patients with chemo-resistant HIV/AIDS-associated tuberculosis disseminated (57.3%) and fibro-cavernous forms of lungs tuberculosis (28.5%) prevailed significantly (P <0.05) more often. There are 3 patients (13.6%), who interrupted treatment, 1 patient refused treatment completely. Antiretroviral therapy was received by 4 patients (28.5%), 1 patient (7,1%) renounced, in 9 cases (64.4%) - antiretroviral therapy was not intended. The autopsy determined that 14 (100%) patients died due to progression of tuberculosis. Conclusion. It was determined that most of the patients lived the anti-social way of life, and suffered from alcoholism or drug addiction. More often co-infected patients with chemo-drug resistant tuberculosis suffered from tuberculosis earlier, than from HIV, most of the patients had chronic tuberculosis. They had interruptions and failures in previous treatment; most of the patients who died from co-infection had MRTB with resistance to 8-9 anti-TB drugs and all of those patients had pulmonary tuberculosis and predominantly disseminated and fibro-cavernous forms, they had a low level of CD4+ cell. Most patients had noncompliance with a specific anti-TB and antiretroviral treatment and did not receive preventive treatment.